Comparison of infection control practices in dental radiographic examination during the COVID-19 pandemic among various health facilities in Yogyakarta, Indonesia - Dewangga, Mella Anggia Puspa; Shantiningsih, Rurie Ratna; Widyaningrum, Rini; Yanuaryska, Ryna Dwi (Majalah Kedokteran Gigi Indonesia, 2024)
Dental radiography services were at high risk of becoming sites for cross-infection during the COVID-19 pandemic. To minimize the spread of COVID-19, infection control adaptations were implemented in dental radiography services across various healthcare facilities, including Type A, B, C, and D hospitals, as well as clinical laboratories. This study aims to determine the differences in infection control practices of dental radiographic examinations during the COVID-19 pandemic at various health facilities. This cross-sectional study involved 42 dental radiographers who worked in Yogyakarta. Control infections were measured using the electronic questionnaire with 27 closed-ended questions. The data were analyzed statistically using the Kruskal-Wallis test, and descriptive analysis was continued by categorizing the control infection into high, medium, and low levels. The validity and reliability test showed that 18 questionnaire items were valid and reliable. The statistical test showed a p-value of 0.672 (p > 0.05) for the staff infection control and 0.147 (p > 0.05) for the room infection control. This study found no significant differences in infection control practices during dental radiographic examinations across various healthcare facilities during the COVID-19 pandemic. All facilities implemented high levels of infection control, with clinical laboratories showing the highest compliance. The study suggests increasing the number of questionnaire items related to room infection control and expanding the study’s scope in future research to improve accuracy and represent a broader population.